Five golden principles to advance marine reef restoration by linking science and industry - ter Hofstede, Remment; Bouma, Tjeerd J.; van Koningsveld, Mark (Frontiers in Marine Science, 2023)
Marine reef ecosystems have degraded massively worldwide and restoration efforts have as yet not managed to realize the scale required to reverse continued degradation. To achieve effective scales, scientific insights in restoration methods should be paired with industry-based approaches used for infrastructural development. We illustrate by five principles how long-standing experience of marine contractors with executing large-scale projects, can support reef restoration: i) utilizing industrial techniques to achieve positive impact at scale, ii) landscaping infrastructure to optimize habitat for targeted species, iii) inducing life to overcome connectivity bottle-necks and steer community composition, iv) designing nature development efforts to be self-sustainable, and v) ensuring continuity beyond project boundaries by early stakeholder engagement. Consciously connecting scientific knowledge to industry-based activities increases the likelihood that marine infrastructure development and ecosystem rehabilitation can be aligned. We plead that synergizing practices by science and industry is needed to upscale restoration efforts and truly improve marine reef ecosystems.